A Systematic Review on Validated Precision Livestock Farming Technologies for Pig Production and Its Potential to Assess Animal Welfare - Gómez, Yaneth; Stygar, Anna H.; Boumans, Iris J. M. M.; Bokkers, Eddie A. M.; Pedersen, Lene J.; Niemi, Jarkko K.; Pastell, Matti; Manteca, Xavier; Llonch, Pol (Frontiers in Veterinary Science, 2021)
Several precision livestock farming (PLF) technologies, conceived for optimizing farming processes, are developed to detect the physical and behavioral changes of animals continuously and in real-time. The aim of this review was to explore the capacity of existing PLF technologies to contribute to the assessment of pig welfare. In a web search for commercially available PLF for pigs, 83 technologies were identified. A literature search was conducted, following systematic review guidelines (PRISMA), to identify studies on the validation of sensor technologies for assessing animal-based welfare indicators. Two validation levels were defined: internal (evaluation during system building within the same population that were used for system building) and external (evaluation on a different population than during system building). From 2,463 articles found, 111 were selected, which validated some PLF that could be applied to the assessment of animal-based welfare indicators of pigs (7% classified as external, and 93% as internal validation). From our list of commercially available PLF technologies, only 5% had been externally validated. The more often validated technologies were vision-based solutions (n=45), followed by load-cells (n=28; feeders and drinkers, force plates and scales), accelerometers (n=14) and microphones (n=14), thermal cameras (n=10), photoelectric sensors (n=5), radio-frequency identification (RFID) for tracking (n=2), infrared thermometers (n=1), and pyrometer (n=1). Externally validated technologies were photoelectric sensors (n=2), thermal cameras (n=2), microphone (n=1), load-cells (n=1), RFID (n=1), and pyrometer (n=1). Measured traits included activity and posture-related behavior, feeding and drinking, other behavior, physical condition, and health. In conclusion, existing PLF technologies are potential tools for on-farm animal welfare assessment in pig production. However, validation studies are lacking for an important percentage of market available tools, and in particular research and development need to focus on identifying the feature candidates of the measures (e.g. deviations from diurnal pattern, threshold levels) that are valid signals of either negative or positive animal welfare. An important gap identified are the lack of technologies to assess affective states (both positive and negative states).